On Freud's "Creative writers and day-dreaming" - Person, Ethel Spector; Fonagy, Peter, 1952-; Figueira, Sérvulo A.; Freud, Sigmund, 1856-1939 (Contemporary Freud., 2013)
First presented as an informal lecture in 1907, "Creative Writers and Day-dreaming" pursues two lines of inquiry: it explores the origins of daydreaming and its relation to the play of children, and it investigates the creative process. Following an introduction by Ethel Spector Person, the contributors to this volume provide commentaries on Freud's essay, explicating the twists and turns in psychoanalytic theories of fantasy and in applied psychoanalysis. Their essays place Freud's paper in historical context, describe the clinical value of daydreams and fantasies, offer a Kleinian view of fantasy, provide analytic approaches to creativity and fantasy, comment on the ambiguity caused by multiple translations of Freud's text, and reframe the idea of fantasy from a modern biological and developmental approach.